Developing Augmented Reality-Based Interactive Learning Media to Improve Critical Thinking Skills of Elementary School Students - Sulthon, Ilma Kamila; Nuriman, Nuriman; Handayani, Rif'ati Dina (Jurnal Paedagogy, 2025)
This study aims to develop augmented reality according to interactive learning media to improve the skills of critical thinking of students at elementary school. This research used research and also development by using a 4D model including Define, Design, Develop, and also Disseminate. The data collection technique used questionnaires, observations and tests used for validity tests, practicality tests and effectiveness tests in research. The findings of the study showed that the augmented reality based interactive media of learning developed was included in having an average validity score of 90.01% in the highly valid category. The practicality test based on the findings of student responses and observation of implementation had an average score of 84.03% categorized as highly practical. The effectiveness test of ability of critical thinking analysis resulted in a score of an N-gain of 0.51 in the medium category, which can significantly improve the thinking ability of elementary school students in subjects of science. In short, the use of augmented reality-based interactive learning media in elementary school learning can improve critical thinking skills.